The Origin of German-American Relations as a Partnership of Unequal Parties - E. S. Leonov (Vestnik MGIMO-Universiteta)
Abstract: Despite the high technological effectiveness of today’s German economy which serves as the «engine» of Europe and the core of the European integration processes, Germany, however, possesses a limited foreign policy leverage in the modern international relations. Gradual restriction of the sovereignty of Germany began during the post-war period due to the strengthening of the European track of U.S. foreign policy. For instance, at this stage Washington takes the responsibility on restoration of the German economic welfare, filling of legal vacuum in West Germany and also initiates cultural and ideological expansion. In the latter case it was an important role played by the American course on the formation of the renewed German nation by means of work with the German youth and the control over the sphere of education. In fact, at the end of the war US authorities started in West Germany experimental project from scratch, since there were no state institutions in postwar Germany in principle. At the same time, German foreign policy takes shape in the 1950s in the spirit of «Atlantic solidarity» as a result of falling into the trap of Euro-Atlantic partnership. Hopes of attainment of foreign policy independence as a result of German reunification did not come true - the United States haven’t yet set Germany free from the sphere of its geopolitical influence. American military forces with nuclear component continue to be based within the territory of Germany. In addition, in the 1990s. Germany finds itself in even deeper trade, investment and financial bondage. The article analyzes the origin of German full-scale dependence on U.S. foreign policy.